Performance improvement of pulse width‐amplitude modulation‐based quasi‐Z‐source inverters: Analysis and implementation. (17th June 2020) - Mohammadi, Mohammad; Mirzaee, Afshin; Magnone, Paolo; Moghani, Javad; Mattavelli, Paolo
Summary: Pulse width‐amplitude modulation (PWAM) have been widely used in recent years to mitigate switching losses as well as reducing passive components' size. This paper precisely investigates this modulation approach in quasi‐Z‐source inverters (qZSI). It will be concluded that the existence of capacitive paths from load to source in such converters causes two undesired behaviors while utilizing PWAM, which increases total harmonic distortion and semiconductor stresses. Bypassing the capacitive paths is proposed in this paper to alleviate these issues. In order to implement this approach, a bidirectional quasi‐Z‐source inverter is studied. A design procedure is presented to achieve a fast dynamic response for tracking reference voltage. The operation of both conventional and bidirectional qZSI under different loads including resistive and resistive–inductive loads is investigated in the simulation and experiment. According to experimental results, by utilizing bidirectional qZSI, THD is improved from 12.34% to 3.51% for a lag load. Moreover, the voltage stress of the semiconductor no longer exists. Abstract : This paper precisely investigates pulse width‐amplitude modulation approach in quasi‐Z‐source inverters. It will be concluded that using this method in such converters causes two undesired behaviors. A general solution is proposed for solving the problems regarding the use of PWAM in such inverters and then simulation and experimental results are presented in order to confirm the study.